Isolation and identification of Candida spp. from immunocompromised patients - Anas Salama Sayed Hemaid; Mohamed Mahmoud Effat Abdelghany; Tarek Mohamed Abdelghany (Bulletin of the National Research Centre, 2021)
Abstract Background Candida species is considered one of the normal inhabitant commensal microbiota of the human body. However, it can also act as an opportunistic pathogen especially in hospitals (nosocomial infection) and among immunocompromised patients. The accurate, precise, rapid and reliable identification of Candida to the species level is of great importance for control and management of candidiasis. Results One hundred and eighteen different samples were collected (59 urine samples, 39 oral swabs, 5 vaginal swabs and 15 skin swabs) from immunocompromised patients (diabetics—pregnant women—patients underwent organ transplantation—cancer patients—burned and wounded patients) for probable existence of Candida species. Eighty-six out of 118 (72.8%) samples were typed macroscopically and microscopically and found to be Candida species. Upon streaking 86 Candida isolates on CHROMagar plates separately, 48 isolates gave green colonies, 25 isolates gave rose colonies, 10 isolates gave white colonies, 2 isolates gave pale coloured colonies and 1 isolate gave blue colonies. Forty-eight out of 86 isolates showed positive Germ tube test. API 20C assay was performed on some isolates with different coloured colonies, the results were similar to those of CHROMagar. Upon performing PCR assay on 14 isolates using ITS1 and ITS4 primers, 8 out of 14 PCR product bands appeared between 510 and 535 bp and this was difficult to differentiate among them (C. albicans, C. tropicalis, C. krusei and C. parapsilosis). Five out of 14 PCR products were found at 871 bp (C. glabrata) and the last one is negative control with no band appeared. Further molecular studies should be recommended to fully differentiate among Candida species especially those with very close bands. Antifungal activity (expressed by inhibitory zone) of zinc oxide nanoparticles in comparison with some commercially available antifungals (nystatin and Voriconazole) was carried upon the obtained Candida isolates. Zinc oxide nanoparticles with 100 μg/disc showed 9, 26, 40, 42 mm inhibitory zones for C. tropicalis, C. glabrata, C. albicans and C. parapsilosis, respectively. However, zinc oxide only showed no antifungal activity against C. krusei. Conclusions A sheet of identification profile for Candida should include morphotyping, biotyping and genotyping to reach a rapid, reliable and accurate diagnosis. Candida species causes a myriad of infections causing non-invasive, mucocutaneous infections and severe systemic and deep-seated disease. Repress of Candida growth by ZnONPs provides an insight towards their therapeutic application for the prevention of Candida-associated infections. Further studies on the antifungal effect of nanoparticles combined with commercially available antifungal medicines maybe recommended.